Penerapan Metode Simple Additive Weighting (SAW) Dalam Sistem Penunjang Keputusan Untuk Menentukan Tempat Prakerin - Farida, Ida; Asri Wahyuni (LPPM POLITEKNIK LP3I BANDUNG, 2022)
Industrial Work Practice (PRAKERIN) is a way of providing vocational education and training, especially in Vocational High Schools (SMK). SMK Negeri 6 Tangerang Regency is one of the vocational high schools that carry out internship activities for its students. Choosing the right place for students to take part in PRACTICES is a good step so that the criteria needed by the school can be met properly. Simple Additive Weighting (SAW) is a method to support decision-making. Based on the results of data analysis, the recommended order of prakerin places was obtained with the final results obtained where there were three (3) largest values that became a reference place for students of SMK Negeri 6 Tangerang Regency, namely alternative A1 (Ahass Abdi Jaya), A2 (Ahass Ardian 4), and A20 (Ardian II) with a final score of 8. So the school will find it easy to determine the place for internships for students.